Pendidikan Kesehatan dengan Media Slide Efektif dalam Meningkatkan Pengetahuan tentang Perawatan Vulva Hygiene pada Siswi Kelas VIII SMP 2 Sedayu Bantul - Egi Ade S; Wahyuningsih Wahyuningsih; Kayat Haryani (Alma Ata University Press, 2016)
Cervical cancer is one of the main cause of the woman death. Most patients come for treatment is when cancer at an advanced stage, while cervical cancer can be prevented, with early knowledge of the vulva hygine treatment. Appropriate strategies to improve knowledge about cervical cancer prevention is to provide health education. The purpose of this research was to know effectiveness of health education with the media slide in increasing knowledge about vulva hygine treatment at Junior High School 2 Sedayu, Bantul Yogyakarta. The research was pre experiment research. The population in this study were 8th grade students of Junior High School 2 Sedayu Bantul amounted to 69 respondents. Samples was selected by total sampling technique. Data were analyzed using the Wilcoxon statistical test. The results showed that health education with media slide effective increase of knowledge students. In conclusion, health education with media slide was effectively improve the level of knowledge of 8th grade students of Sedayu 2 Junior High School, Bantul Yogyakarta.